Caracterização da digestão de resíduos agroindustriais em biodigestor de fluxo contínuo operado em escala real - Caldereiro, Gisele Maria Brod (2015)
Slaughterhouses are potentially polluting agricultural industries due to the organic load present in the wastewater and solid waste generated in the process. To minimize the environmental impact generated by this type of activity, it is necessary to provide a treatment processes that enables the reduction of the organic matter present in slaughterhouse waste, transforms waste into value-added products and exploits energy use efficiently. The implementation of biodigesters to treat solid waste and wastewater generated in slaughterhouses is an interesting option, given the anaerobic digestion process that makes up the system and the possible benefits it provides. Therefore, the present study evaluated the efficiency of an anaerobic continuous flow digester, in real scale, used for the treatment of solid waste and liquid effluents from the process. In order to do so, physicochemical characterization of the digester feed substrates, as well as, characterization of the influent and effluent of the system were performed. In addition, analyzes were executed to evaluate the characteristics of the bio-fertilizer and biogas originating in the process. The results showed that the digester feed substrate is composed of various origins and, each has a specific and distinct physicochemical characteristic, but when these different characteristics are combined they favor the development of an environment prone to the performance of the anaerobic digestion. By assessing the overall system efficiency, while considering the values obtained for the influent and effluent analysis, some parameters were considered efficient, whereas others result in the increase of concentration. This may have been triggered by factors which are external to the system. The bio-fertilizer originating from the digester was characterized as non-inert solid waste, which might require certain restrictions in its application in soil. Biogas, in turn, presented interesting methane concentration and is therefore likely to be used in various industrial processes.